Diagnostic capability of contrast-enhanced pelvic girdle magnetic resonance imaging in polymyalgia rheumatica. (20th February 2020) - Fruth, Martin; Seggewiss, Annika; Kozik, Jessica; Martin-Seidel, Philipp; Baraliakos, Xenofon; Braun, Juergen
Abstract: Objective: There is currently no diagnostic test for PMR. A characteristic pattern of extracapsular inflammation as assessed by contrast-enhanced MRI (ceMRI) has recently been described in the pelvis of patients with PMR. We aimed to evaluate the performance of inflammatory ceMRI signals at predefined pelvic sites as a diagnostic test for PMR. Methods: Pelvic MRI scans of patients with pelvic girdle pain ( n  = 120), including 40 patients with an expert diagnosis of PMR and 80 controls with other reasons for pelvic pain were scored by three blinded radiologists, who evaluated the degree of contrast enhancement at 19 predefined tendinous and capsular pelvic structures. Different patterns of involvement were analysed statistically. Results: The frequency of bilateral peritendinitis and pericapsulitis including less common sites, such as the proximal origins of the m. rectus femoris and m. adductor longus, differed significantly between PMR cases and controls: 13.4 ± 2.7 vs 4.0 ± 2.3. A cut-off of ≥10 inflamed sites discriminated well between groups (sensitivity 95.8%, specificity 97.1%). Bilateral inflammation of the insertion of the proximal m. rectus femoris or adductor longus tendons together with ≥3 other bilaterally inflamed sites performed even better (sensitivity 100%, specificity 97.5%). Conclusion: This study confirms that a distinctive MRI pattern of pelvic inflammation (bilateral peritendinitis and pericapsulitis and the proximal origins of the m. rectus femoris and m. adductor longus) is characteristic for PMR. The high sensitivity and specificity of the set of anatomical sites evaluated suggests their clinical usefulness as a confirmatory diagnostic test.